2021
DOI: 10.21037/atm-20-7019
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted balance of long and short-range functional connectivity density in Alzheimer’s disease (AD) and mild cognitive impairment (MCI) patients: a resting-state fMRI study

Abstract: Background: Alzheimer's disease (AD) is an age-progressive neurodegenerative disorder that affects cognitive function. There have been several functional connectivity (FC) strengths; however, FC density needs more development in AD. Therefore, this study wanted to determine the alternations in resting-state functional connectivity density (FCD) induced by Alzheimer's and mild cognitive impairment (MCI).Methods: One hundred and eleven AD patients, 29 MCI patients, and 73 healthy controls (age-and sexmatched) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…This finding was consistent with previous research on topological changes in the functional connectome, which revealed that increased nodal properties such as global nodal efficiency and nodal strength in the SCD were primarily found in the default mode network (DMN), including the medial temporal and PHG (Li et al, 2018b ; Chen et al, 2020a ). However, in patients with aMCI, the gFCD of the PHG was markedly decreased compared with patients with SCD, a trend consistent with the previous studies (Liu et al, 2016 ; Mao et al, 2021 ; Yuan et al, 2021 ). This result suggested that, as the disease progressed, functional compensations became insufficient to compensate for further neurological damage, resulting in objective impairment in cognitive domains.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding was consistent with previous research on topological changes in the functional connectome, which revealed that increased nodal properties such as global nodal efficiency and nodal strength in the SCD were primarily found in the default mode network (DMN), including the medial temporal and PHG (Li et al, 2018b ; Chen et al, 2020a ). However, in patients with aMCI, the gFCD of the PHG was markedly decreased compared with patients with SCD, a trend consistent with the previous studies (Liu et al, 2016 ; Mao et al, 2021 ; Yuan et al, 2021 ). This result suggested that, as the disease progressed, functional compensations became insufficient to compensate for further neurological damage, resulting in objective impairment in cognitive domains.…”
Section: Discussionsupporting
confidence: 90%
“…Such a result was not unexpected, as there were no abnormalities in patients with SCD on the neuropsychological scales (Liang et al, 2020 ; Chen et al, 2021b ). Because there are no effective and objective methods for diagnosing SCD or determining whether patients with SCD have been exacerbated, existing studies have attempted to improve disease differentiation accuracy by combining multiple indicators (Hadjichrysanthou et al, 2020 ; Parker et al, 2020 ; Mao et al, 2021 ). By ROC analysis, Xue et al ( 2021 ) combined abnormal FC of the abnormal salience network, ALFF, and gray matter volume with the AUC value up to 0.852 in the SCD and HC groups and combined scale assessment results, cortical thickness of abnormal brain regions, and FC changes with the AUC value up to 0.931 in the SCD and aMCI groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major function of the superior temporal gyrus is extracting meaningful linguistic features from speech inputs, and is strongly modulated by learning knowledge and perceived goals ( Zhongwei et al, 2017 ). There is some evidence that the right STG functions in allocentric neglect deficits ( Mao et al, 2021 ). The significantly lower signal in this region in the MCI group in the present study may be related to the altered perception of language in patients with MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, resting state functional connectivity density (rsFCD) was proposed to provide a comprehensive analytical method for brain's "scale-free" networks by comparing differences in functional connectivity between the whole brain and the given voxel in a high spatial resolution During the past few years, FCD mapping has proven to be instructive in diagnosing and providing supplementary evidences for symptom improvement of several psychiatric disorders such as depression and schizophrenia [6,9,10], and there were also studies investigating smoking and internet addiction had applied FCD to demonstrate the link between the aberrance in brain functional connectivity and addictive behaviors [11,12]. Although several FCD researches were conducted on AUD, these studies focused on the early diagnose and assessment [13,14] instead of probing into the correlation of pathological changes in functional connectivity with the development of AUD.…”
Section: Introductionmentioning
confidence: 99%